Changing the Educational Culture of the Home to Increase Student Success at School - Kenneth Leithwood; Penny Patrician (Societies, 2015)
Parent involvement in their children’s learning is widely acknowledged as having a positive effect on student academic success. Of particular relevance is the finding that the influence of parent engagement can mitigate differences in socioeconomic status (SES) and family background. Family background is a multi-dimensional concept that includes the family’s “educational culture” (including for example, parenting style, parental expectations for children’s work at school, direct instructional support for school learning, active parent interest in the school’s curriculum, and the monitoring of children’s engagement with their school work). It is these features of a child’s home environment that directly influence much of the social and intellectual capital students need to be successful at school. This paper summarizes a quasi-experimental field study which explored the relative effects of alternative types of school interventions on parent engagement. All of these interventions aimed to further engage parents in the education of their children as a means of both improving student achievement and closing gaps in achievement for students living primarily in challenging social and economic circumstances. Initiatives by school staffs aimed at helping those families struggling to build productive educational cultures in their homes would appear to be a very promising strategy for closing achievement gaps between advantaged and disadvantaged students. The study provides eight lessons other districts might take heed of as they embark on their own parent engagement interventions.